Marchas de crescimento e de acúmulo de nutrientes do capim-elefante - Morais, Éric George (2021)
By knowing more accurately the dynamics of growth and accumulation of nutrients by elephant grass, it is possible to offer nutrients according to the plant's demand, especially in the phases or intervals of greatest nutritional demand. Thus, it is possible to suggest more appropriate fertilization recommendations for this crop, avoiding underestimating or overestimating the recommended nutrient doses. Therefore, the objective was to evaluate the accumulation of dry matter and nutrients of elephant grass cv. Cameroon, grown in a Quartzene Neossolo. Elephant grass was grown under field conditions in four plots of 27 m2 (3.0 x 9.0 m) during two cultivation cycles, corresponding to four replications. In each of these plots, destructive sampling of plants was carried out at different times to assess the accumulation of dry matter and nutrients in the aerial part of the plants. In the first cultivation cycle, the plants were collected at 21, 35, 49, 63, 77, 91, 105 and 119 days after planting. Samples of plants from the second cycle were carried out at 21, 35, 49, 63, 77, 91 and 105 days after the uniform cut. In all collections, the number of tillers per linear meter was estimated and the following characteristics were evaluated: plant height, dry matter weight of the aerial part and the levels of macronutrients (N, P, K, Ca, Mg and S) and micronutrients (Fe, Cu, Mn and Zn) in the dry matter of the aerial part of elephant grass plants. The total accumulation of macronutrients by elephant grass accompanied the accumulation of dry matter in the aerial part. The period of greatest growth of elephant grass occurred from 18 to 102 days in the 1st cycle, and in the 2nd cycle from 8 to 61 days. At the end of the first and second cycle, elephant grass had a total dry matter production of 32.62 and 39.42 t ha-1, respectively. The highest daily accumulation rates occurred around 60 days after planting or cutting. The accumulation of macronutrients in the aerial part of elephant grass cv. Cameroon presented the following decreasing order: K > N > Mg > Ca > P > S, in both cycles. The accumulation of micronutrients in the aerial part of elephant grass cv. Cameroon presented the following decreasing order: Fe > Mn > Zn > Cu, and, Fe > Zn > Mn > Cu, in the first and second cycles, respectively